2020
DOI: 10.1155/2020/8881273
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of SiO2‐Coated Carbon Fiber‐Reinforced Mortar Composites with Different Fiber Lengths and Fiber Volume Fractions

Abstract: In the present study, SiO2 particles were coated on the surface of carbon fibers by means of chemical reaction of silane coupling agent (glycidoxypropyl trimethoxysilane, GPTMS) and colloidal SiO2 sol to improve the interfacial bonding force between fibers and matrix in cement matrix. The surface of the modified carbon fibers was confirmed through a scanning electron microscope (SEM). The mechanical properties of SiO2-coated carbon fiber mortar and uncoated carbon fiber mortar with different fiber lengths (6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
(32 reference statements)
6
2
0
Order By: Relevance
“…However, the average flexural strength of a hybrid FRM reinforced with 25% steel fibers + 75% carbon fibers was measured to be 5.88 MPa, and the average flexural strength of a single FRM reinforced with only carbon fiber showed a little decrease. Such a result as this was also reported in previous studies [54,55], and it is thought because reinforced fibers prevented growth of cracks by playing a crosslinking role and, by thus, improved the flexural strength by means of redistribution of stress. It is possible to obtain a mutual synergy effect of fiber reinforcement by combining macrosteel fibers having large length and diameter with microcarbon fibers having small length and diameter because the flexural strength would increase once fibers are mixed in an appropriate ratio even when the portion of mixed fibers is small.…”
Section: Compressive Strengthsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the average flexural strength of a hybrid FRM reinforced with 25% steel fibers + 75% carbon fibers was measured to be 5.88 MPa, and the average flexural strength of a single FRM reinforced with only carbon fiber showed a little decrease. Such a result as this was also reported in previous studies [54,55], and it is thought because reinforced fibers prevented growth of cracks by playing a crosslinking role and, by thus, improved the flexural strength by means of redistribution of stress. It is possible to obtain a mutual synergy effect of fiber reinforcement by combining macrosteel fibers having large length and diameter with microcarbon fibers having small length and diameter because the flexural strength would increase once fibers are mixed in an appropriate ratio even when the portion of mixed fibers is small.…”
Section: Compressive Strengthsupporting
confidence: 89%
“…It is judged that the compressive strength decreased because the interfacial bonding strength between the fibers and matrix in the mortar after hardening was weak due to the nonhydrophilic material on the fiber surface. e results of this kind were also reported in previous studies [54,55], which pointed out that when a large amount of fiber was used, the dispersibility of fibers decreased, generating in more and more fiber balls as a result, which greatly affected to decrease the compressive strength. In this experiment, therefore, the optimum fiber combination to obtain the maximum compressive strength is 75% steel fibers + 25% carbon fibers.…”
Section: Compressive Strengthsupporting
confidence: 76%
“…It is judged that the strength of carbon fiber was reduced because the interfacial bonding force between the fiber and matrix in the mortar after hardening was weak due to the non-hydrophilic material on the fiber surface. These results have also been reported in previous studies [21][22][23] which pointed out that, due to high rate of mixed fibers, dispersibility of fibers is lowered, resulting in more and more ball of fibers and greatly affecting decrease in the compressive strength. In this experiment, the optimum mixture ratio to obtain the maximum compressive strength was found to be SF-CF=75-25%.…”
Section: Compressive Strengthsupporting
confidence: 88%
“…This indicates a higher flexural strength as the micro CF bears the stress when the initial crack occurs. As was also reported in previous studies [22][23], such result is considered to be related to the fact that mixed fibers prevented propagation of cracks by bridging effect and the flexural strength was improved by redistribution of stress. Therefore, the synergy effect of fiber reinforcement can be obtained by increasing the flexural strength if fiber is mixed in an appropriate ratio even if the mixture ratio of the fiber is small through combination of macro SF of large length and diameter and micro CF of small length and diameter.…”
Section: Flexural Strengthsupporting
confidence: 79%
“…The mechanical properties of CFRC are well related to the interfacial bonding strength between CFs and cement paste. Heo et al [ 41 , 60 ] designed a unique treatment method that can uniformly coat nano-SiO 2 particles on the surface of CFs for hydrophilic modification based on the chemical reaction of a silane coupling agent. It was concluded that the significant improvement in the chemical binding force of the interface transition zone could be achieved through the C-S-H gel formed by the reaction of nano-SiO 2 and Ca (OH) 2.…”
Section: Property Evaluation Of Cfrcmentioning
confidence: 99%